(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The paper focuses on the growth of the agricultural sector from the past to current trends and its growth in smart farming. The agriculture sector in India has successfully met the production targets set by the government and has also set new production records in almost all commodities. The paper is a bibliometric analysis of the systematic literature review of precision agriculture, including technical terms like IoT, precision agriculture, machine learning, artificial intelligence, and traditional farming. The paper discusses the various phases in the agricultural management system, including advancements from the past centuries to current trends.